Stanje raziskav o proznih delih sodobnih slovenskih pisateljic - Kraner, Tina (Slavia Centralis, 2020)
STATE OF RESEARCH OF PROSE WORKS WRITTEN BY CONTEMPORARY SLOVENIAN FEMALE WRITERS The article provides an insight into the present state of research in prose works written by contemporary Slovenian female writers. In Slovenia, this kind of research started to emerge relatively late compared to some other European countries (e.g. Germany, England and France). However, interest in the so-called women’s writing has been growing. Works by contemporary Slovenian female writers have become an interesting topic of research, as evidenced by numerous scientific monographs, articles, literary criticisms, reviews and, last but not least, bachelor’s and master’s theses and doctoral dissertations.